Study on Structural Properties of Concrete by Partial Replacement of Fly Ash - A Study - Mr. Ram Ditta, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
A basic mix design process described by Okamura (Japanese method) was applied in the current study. In this study, a variety of SCC mixes were created utilising fly ash as a partial replacement for Portland cement of grade 43. The purpose of this study is to construct a viable mix design to meet the criteria of Self Compacting Concrete with Flyash as a partial replacement in the plastic stage utilising local aggregates, and then to determine the compressive, split tensile, and flexural strengths. To determine the suitability of selfcompacting concrete mixtures Slump flow, V-funnel, L-Box, and U-Box tests were carried out, and the results were compared to the EFNARC guidelines' criteria. Fly ash was replaced in 10%, 20%, and 30% by the weight of cement. Also, to determine the strength attributes of the mixtures after 7, 14, 21, and 28 days after curing. It was discovered that Fly ash may be substituted up to 10% in SCC to provide a satisfactory mix similar to SCC without Fly ash. The Compressive strength of SCC with 10% Fly ash substitution is the same as normal SCC without Fly ash.